Strategies for Reducing Greenhouse Gas Emissions and Promoting Renewable Energy - Mamta Mudaliyar; Anushree Sharma; Akshara Panja (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
As the effects of climate change become more severe, environmental sustainability has become an urgent problem in public administration. The purpose of this research is to examine the approaches taken by governmental agencies to lessen their carbon footprints and boost renewable energy sources. The methodology incorporates a survey of relevant literature, an examination of relevant policies and laws, and a comparison of various national approaches. The findings demonstrate that carbon pricing and emissions trading systems are useful instruments for encouraging reductions in emissions, though their applicability may be constrained in some settings. Investment and deployment of renewable energy technologies can be prompted by goals for increased use of such sources, as well as by financial incentives and regulatory support. Investment in distributed renewable energy systems is encouraged by feed-in tariffs and net metering, but these policies may have unintended effects. There is a great deal of diversity in the policies and strategies employed by various nations, but there are also many similarities and shared experiences that can be used to create more effective policies. The research highlights the importance of public management in developing and implementing policies and strategies to combat climate change. The results are instructive for academics, policymakers, and practitioners in their pursuit of better methods of lowering carbon emissions and advancing sustainable energy.